A simple approach to synthesize novel sulfur/graphene oxide/multiwalled carbon nanotube composite cathode for high performance lithium/sulfur batteries - Yuan, Guanghui; Zhao, Yan; Jin, Huafeng; Bakenov, Zhumabay (Ionics, 2016)
A sulfur/graphene oxide/multiwalled carbon nanotube (S/GO/MWNT) composite was synthesized via a simple ultrasonic mixing method followed by heat treatment. By taking advantage of this solution-based self-assembly synthesis route, poisonous and noxious reagents and complicated fabrication processes are rendered unnecessary, thereby simplifying its manufacturing and decreasing the cost of the final product.
Keywords: Electrochemical performance; Lithium/sulfur battery; Ultrasonic mixing